Struktur Dan Desain Bangunan Tradisional Bali Di Banjar Cekeng, Desa Sulahan, Bali - Made Novia Indriani; Ida Ayu Putu Sri Mahapatni1; I Putu Laintarawan; I Wayan Artana (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2023)
The structure and design of traditional Balinese buildings are still great features, especially when it comes to keeping culture, society, and religion alive in old buildings. Research on building design structures still needs to be reported. This study aims to analyze the structure and design of traditional Balinese buildings in Banjar Cekeng, Sulahan Village, Bali. The mixed method study design was used to direct residents of Br Cekang to sekanem and Paon buildings. Data analysis is carried out descriptively. As a result, the traditional Balinese structure and design of the Sakanem and Paon (kitchen) in Banjar Cekeng meet SNI based on structural analysis. The findings show the strength of the structure for the beams and that the bale Sakanem and Paon horses have sufficient vertical rigidity to withhold the working boundary loads. Furthermore, at the lateral deviation of the Sakanem and Paon building structures, they have sufficient lateral rigidity to withstand the earthquake loads in the x and y directions. Maximum factored force analysis obtained the results of the structures of models 1 (Sakanem), consisting of column and beam structure components made of wooden material, and models 2 (Paon), with concrete column structure components, bamboo, and wooden beams. The nominal bending and sliding capacities of Sakanem and Paon beams are greater than the ultimate bending and sliding capacities. The combined capacity of bending and axial columns in Sakanem and Paon buildings is smaller than the bending and axial capacity of ultimate and practical columns in Paon buildings, not crossing the interaction boundary line.